2008
DOI: 10.1073/pnas.0800371105
|View full text |Cite
|
Sign up to set email alerts
|

Naturally acquired Duffy-binding protein-specific binding inhibitory antibodies confer protection from blood-stage Plasmodium vivax infection

Abstract: Individuals residing in malaria-endemic regions acquire protective immunity after repeated infection with malaria parasites; however, mechanisms of protective immunity and their immune correlates are poorly understood. Blood-stage infection with Plasmodium vivax depends completely on interaction of P. vivax Duffy-binding protein (PvDBP) with the Duffy antigen on host erythrocytes. Here, we performed a prospective cohort treatment/reinfection study of children (5-14 years) residing in a P. vivax-endemic region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
209
3
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(234 citation statements)
references
References 24 publications
8
209
3
8
Order By: Relevance
“…Of these 18 studies, 9 were cross-sectional, 6 were cohort (4 of which also provided cross-sectional data), and 3 were case-control studies. One cohort study contributed two publications [34,35], and one publication provided data from two countries [22]. For the purpose of this review, we shall refer to each publication as a study.…”
Section: Identification and Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 18 studies, 9 were cross-sectional, 6 were cohort (4 of which also provided cross-sectional data), and 3 were case-control studies. One cohort study contributed two publications [34,35], and one publication provided data from two countries [22]. For the purpose of this review, we shall refer to each publication as a study.…”
Section: Identification and Description Of Included Studiesmentioning
confidence: 99%
“…The full texts of these 162 studies were examined to determine whether they complied with eligibility criteria: 114 did not meet the inclusion criteria (see Additional file 3), 7 fulfilled the inclusion and quality criteria (Figure 1), and 41 studies potentially met inclusion and quality criteria. The authors of the 41 studies that potentially met inclusion and quality criteria were contacted, yielding a further 11 studies that met inclusion and quality criteria, providing a total of 18 studies that were included in the review [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] (Figure 1). Details of these 18 studies are shown in Table 1.…”
Section: Identification and Description Of Included Studiesmentioning
confidence: 99%
“…Analysis of 676 bp within DBP-II revealed 127 polymorphic sites with nucleotide diversity varying between 0.006 and 0.0109, resulting in 193 haplotypes (35). These factors induce strain-specific protection rather than strain-transcending immunity, which leaves individuals susceptible to continued infection and disease (6,9,17,32,33,36).…”
mentioning
confidence: 99%
“…Both cost-effective and efficient, vaccines are among the leading avenues of intervention, and individuals living in regions with P. vivax develop naturally acquired humoral immunity that correlates with results from in vitro functional assays (6)(7)(8)(9). A leading vaccine candidate for P. vivax is the Duffy Binding Protein (DBP) (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), a parasite cell surface protein in the Erythrocyte Binding-Like (EBL) invasion protein family (14,(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Naturally acquired antibodies to DBP seem to confer protection from blood-stage P. vivax infection, supporting the development of a vaccine against P. vivax malaria [18]. However other studies also pinpointed that produced human antibodies might have low efficiencies underlining the difficulty of vaccine design [19].…”
Section: Duffy Antigensmentioning
confidence: 99%